2022
DOI: 10.7554/elife.77665
|View full text |Cite
|
Sign up to set email alerts
|

DIP2 is a unique regulator of diacylglycerol lipid homeostasis in eukaryotes

Abstract: Chain-length specific subsets of diacylglycerol (DAG) lipids are proposed to regulate differential physiological responses ranging from signal transduction to modulation of the membrane properties. However, the mechanism or molecular players regulating the subsets of DAG species remains unknown. Here, we uncover the role of a conserved eukaryotic protein family, DISCO-interacting protein 2 (DIP2) as a homeostatic regulator of a chemically distinct subset of DAGs using yeast, fly and mouse models. Genetic and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…DIP2C encodes a highly expressed protein in the brain and a member of the highly conserved DIP2 (Disco-interacting protein 2) family implicated in neuronal morphology and development and lipids’ metabolism (Ma et al 2019 ; Mondal et al 2022 ; Mukhopadhyay et al 2002 ; Nitta et al 2017 ; Noblett et al 2019 ; Oo et al 2020 ). A previous study reported 19 patients with submicroscopic deletion of chromosome 10p15.3 that included DIP2C and/or ZMYND11 in all the cases.…”
Section: Discussionmentioning
confidence: 99%
“…DIP2C encodes a highly expressed protein in the brain and a member of the highly conserved DIP2 (Disco-interacting protein 2) family implicated in neuronal morphology and development and lipids’ metabolism (Ma et al 2019 ; Mondal et al 2022 ; Mukhopadhyay et al 2002 ; Nitta et al 2017 ; Noblett et al 2019 ; Oo et al 2020 ). A previous study reported 19 patients with submicroscopic deletion of chromosome 10p15.3 that included DIP2C and/or ZMYND11 in all the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The neuronal defects observed in dip-2(0) sax-2(0) double mutants are generally a combination of more severe or more penetrant versions of the single mutant phenotypes, suggesting that DIP-2 and SAX-2 play partly redundant roles in maintenance of neuronal morphology. The orthologs of DIP-2 function in lipid metabolism 25 , whereas SAX-2/Fry family members are thought to have multiple functions including as scaffolds for SAX-1/NDR kinases 20 . We find that overexpression of DIP-2 did not compensate for loss of SAX-2.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila 23 and in vertebrates 24 . DIP2 family members are thought to regulate the activation of fatty acids and/or accumulation of diacylglycerol via their adenylate-forming domains (AFDs), also known as fatty acyl-AMP ligase-like (FAAL-like, FLD) domains 25 .…”
Section: Dip2 Proteins Function In Neuronal Morphology Maintenance An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al, 2019;Mondal et al, 2022;Mukhopadhyay et al, 2002;Nitta et al, 2017;Noblett et al, 2019;Oo et al, 2020). A previous study reported 19 patients with submicroscopic deletion of chromosome 10p15.3 that included DIP2C and/or ZMYND11 in all the cases.…”
mentioning
confidence: 94%